Bis(pentafluorophenyl)phenothiazylborane – an intramolecular frustrated Lewis pair catalyst for stannane dehydrocoupling. Issue 45 (5th March 2020) - Bentley, Jordan N.; Pradhan, Ekadashi; Zeng, Tao; Caputo, Christopher B.
Abstract : A Lewis acidic aminoborane (1 ) was shown to catalytically dehydrocouple stannanes through an unexpected heterolytic frustrated Lewis pair mechanism rather than a homolytic process. Abstract : We synthesized a novel Lewis acidic aminoborane containing a phenothiazyl substituent and demonstrated its potential to catalytically promote the dehydrocoupling of tin hydrides. The observed reactivity would imply a homolytic frustrated Lewis pair type mechanism, however computational analysis suggests a heterolytic mechanism for this reaction. This result represents one of the first frustrated Lewis pair systems to dehydrocouple stannanes in a heterolytic fashion.